PENGARUH KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION - Firdaus Firdaus; Herlina Lusiana (Islamic University of Kalimantan MAB Banjarmasin, 2020)
This study aims: (1) To test organizational commitment has a positive and significant effect on turnover intention at PT Decorindo Inti Alam Wood South Kalimantan; (2) To test job satisfaction has a positive and significant effect on turnover intention at PT Decorindo Inti Alam Wood South Kalimantan; (3) To test organizational commitment and job satisfaction simultaneously affect turnover intention at PT Decorindo Inti Alam Wood, South Kalimantan. This research was conducted at PT Decorindo Inti Alam Wood, South Kalimantan. There were 78 respondents who were selected as samples using the Slovin formula and random sampling techniques. The research method uses survey methods and types of quantitative research. While the nature of this research includes explanatory research. The data collection method uses a questionnaire, while the data analysis technique uses multiple linear regression analysis, hypothesis testing and coefficient of determination using the IBM Version 24 SPSS program. The results of the study are: (1) Organizational commitment has a positive and significant effect on turnover intention at PT Decorindo Inti Alam Wood in South Kalimantan, as evidenced by the significance of 0,000 <0.05 so the first hypothesis (H1) is accepted; (2) Job satisfaction has a positive and significant effect on turnover intention at PT Decorindo Inti Alam Wood in South Kalimantan, as evidenced by the significance of 0,000 <0.05 so the second hypothesis (H2) is accepted; (3) Organizational commitment and job satisfaction have a simultaneous effect on turnover intention at PT Decorindo Inti Alam Wood in South Kalimantan, as evidenced by the significance of 0,000 <0.05 so the third hypothesis (H3) is accepted. Keywords: organizational commitment; job satisfaction; turnover intention.